The Effect of Different Substrat of Culture of Nereis sp. - Dodi Hermawan (Jurnal Perikanan dan Kelautan, 2015)
Polychaeta is one of aquaculture commodity which is used as feed for shrimp broodstock, fish feed, biofilter, bioindicator and some species can be consumed by humans. The lack of information about polychaeta culture in Indonesia, become the point of interest of this research. The aims of this study is to determine the substrate type as a culture media. The research uses a different type of substrates such as mangrove mud, white sand and brown sand, with three time replication. The research conduct the Laboratory of Aquaculture, Fisheries Department, Sultan Ageng Tirtayasa University. Survival rate and spesific growth rate was measured as a research parameters. The methods used in this research is a completely randomized design (CRD). The results showed the use of mangrove mud as a substrate there are significantly different (P<0.05). Give the best result with the value of survival rate 85.18%±3.21 and spesific growth rate 3.36%±0.71. Based on the results of the research indicate that the use of substrates mangrove mud gives the best effect.